El Excentrico, 1976-11-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, CA, 2024)
November 20, 1976 [20 de noviembre de 1976]. Ano 27, No 15. Cover contains an advertisement for musical performances by Mazacote and his orchestra, as well as Tata Ramos. This event was hosted by entrepreneurs Victor and Arthur. It would take place four days per week until December 26, 1976.